Land Degradation Situation in Bangladesh and Role of Agroforestry - Hasan, MK; Alam, AKM Ashraful (Journal of Agriculture & Rural Development, 2008)
Degradation of land is a vital issue throughout the world with the particular references to Bangladesh as it a threat to agricultural productivity. Agroforestry, a land use system is being popular in many countries to protect the land from various types of degradation. Studies have proved that agroforestry can check soil erosion to some extent, increase soil fertility, reduce salinity, alkalinity, acidity and desertification etc. ultimately improve soil health which keep the land suitable for agricultural production. The article has drawn on the basis of various reviews focusing the land degradation situation of Bangladesh and potentialities of agroforsetry. Key words: Land degradation, desertification, agroforestry.